Pengaruh Financial Knowledge, Pendapatan dan Gaya Hidup Terhadap Financial Management Behavior Nasabah Cabang Pegadaian Syariah (CPS) Bengkulu - Wardani, Anggun Citra; Arisandi, Yossi; Arisandi, Debby (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to analyze the influence of financial knowledge, income, and lifestyle on the financial management behavior of customers of the Bengkulu Islamic pawnshop branch (CPS). This study uses a descriptive quantitative approach with data collection techniques through questionnaires. The population of the study was all CPS Bengkulu customers, with a sample of 80 respondents. Data were analyzed using data quality tests, classical assumption tests, multiple linear regressions, and hypothesis tests. The results showed that financial knowledge had a significant effect on financial management behavior, indicated by a t-value of 3.459 and a significance of 0.001 (<0.05). This indicates that the higher the financial knowledge, the better the customer's financial management behavior. On the other hand, income did not have a significant effect, with a significance value of 0.086 (>0.05), which means that the size of income does not determine good financial behavior. Meanwhile, lifestyle was proven to have a significant effect on financial management behavior with a t-value of 4.354 and a significance of 0.000. The conclusion of this study is that financial knowledge and lifestyle play an important role in shaping healthy financial behavior, while income is not the main factor. Financial education and the formation of a frugal lifestyle need to be improved to encourage better financial management among customers.